2018
DOI: 10.1002/ange.201710144
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Multifunctional RNAi Nanomedicine To Concurrently Target Cancer Hallmarks for Combinatorial Therapy

Abstract: Cancer hallmarks allowt he complexity and heterogeneity of tumor biology to be better understood, leading to the discovery of various promising targets for cancer therapy. An amorphous iron oxide nanoparticle (NP)-based RNAi strategy is developed to co-target two cancer hallmarks.T he NP technology can modulate the glycolysis pathway by silencing MCT4 to induce tumor cell acidosis,a nd concurrently exacerbate oxidative stress in tumor cells via the Fenton-like reaction. This strategy has the following features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The MCT4 silencing can inhibit the efflux of lactate/H + generated by glycolysis of tumor to induce acidosis of tumor cell, meanwhile, result in oxidative damages to tumor cells by enhancing the Fenton‐like reaction. [ 249 ] It can be seen that regulating pH value to optimize reaction parameters of catalytic nanomedicines may be a potential approach to enhance ROS‐induced toxic therapy. Nevertheless, in biological system, it is difficult to regulate the intracellular pH level.…”
Section: Principles For the Design Of Ros‐associated Nanomedicinesmentioning
confidence: 99%
“…The MCT4 silencing can inhibit the efflux of lactate/H + generated by glycolysis of tumor to induce acidosis of tumor cell, meanwhile, result in oxidative damages to tumor cells by enhancing the Fenton‐like reaction. [ 249 ] It can be seen that regulating pH value to optimize reaction parameters of catalytic nanomedicines may be a potential approach to enhance ROS‐induced toxic therapy. Nevertheless, in biological system, it is difficult to regulate the intracellular pH level.…”
Section: Principles For the Design Of Ros‐associated Nanomedicinesmentioning
confidence: 99%
“…Iron ions released from amorphous iron oxide then react with H 2 O 2 to generate highly reactive and toxic OH • via the Fenton reaction. According to in vivo results, suppression of tumor growth was observed for the amorphous iron oxide-RNAi treated group, without causing a noticeable influence on the subjects body weight …”
mentioning
confidence: 95%
“…Toxicity results showed that the viability of MCF-7 cells dramatically decreased from 90 to 26% as the nanoparticle concentration increased from 10 to 100 μg/mL . Recently, Liu et al developed an amorphous iron oxide-RNAi platform coated with lipid-PEG for cotargeting metabolic and hydroxyl radical homeostasis in tumor cells . In this method, RNAi is able to silence MCT4 to induce tumor cell acidosis and H 2 O 2 production.…”
mentioning
confidence: 99%
“…35−39 Additionally, insufficient acidity in TME directly results in low Fenton reaction rates catalyzed by ironcontaining nanoparticles. 40,41 Last but not least, the electron transfer process from Fe 3+ to Fe 2+ is very slow (0.002−0.01 M −1 s −1 ), 42−44 which also hindered the efficiency of ROS production.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being promising, there are still some critical challenges for improving the therapeutic efficacy of the iron-based CDT theranostic nanoplatforms . For instance, abundance glutathione (GSH) produced by tumor would scavenge •OH and reduce oxidative stress. Meanwhile, endogenous H 2 O 2 is insufficient to support continuous •OH production. Additionally, insufficient acidity in TME directly results in low Fenton reaction rates catalyzed by iron-containing nanoparticles. , Last but not least, the electron transfer process from Fe 3+ to Fe 2+ is very slow (0.002–0.01 M –1 s –1 ), which also hindered the efficiency of ROS production.…”
Section: Introductionmentioning
confidence: 99%